Inheritance of drought tolerance in cowpea - Mai-Kodomi, Y.; Singh, B.; Terao, T.; Myers, O.; Yopp, J.H.; Gibson, P.J. (2000)
This study was undertaken to elucidate the nature of inheritance of the two types of drought tolerance in cowpea {Vigna unguiculata (L.) Walp} so that the drought tolerant can be effectively used in breeding programme. Three cowpea lines viz TVu 11986 willi ‘Type l' drought tolerance, Dan IIa with ‘Type 2' drought tolerance and TVu 7718 as susceptible to drought were crossed in all possible combinations. The genetic segregation revealed that drought tolerance is a dominant trait and both ‘Type I' and ‘Type 2' reactions are controlled by a single dominant gene but the genes are different in the two types. These are being designated as ‘Rds 1' (resistance to drought stress) and ‘Rds 2'. Test of allelism indicated that ‘Type 1' is dominant over ‘Type 2' and the F2 population between the two types segregated to 3 ‘Type 1': 1 ‘Type 2' plants indicating that the two genes for drought tolerance are either alleles at the same locus or tightly liriked. Efforts are being made to transfer these genes into improved varieties. However, due to allelic relationship, or close lirikage, both types of drought tolerance may not be bred in the same cowpea line.